Auditory change‐related cortical response is associated with hypervigilance to pain in healthy volunteers. (22nd September 2021) - Otsuru, Naofumi; Ogawa, Mayu; Yokota, Hirotake; Miyaguchi, Shota; Kojima, Sho; Saito, Kei; Inukai, Yasuto; Onishi, Hideaki
Abstract: Background: Patients with chronic pain exhibit hypervigilance (heightened responsiveness to stimuli) to innocuous auditory stimuli as well as noxious stimuli. "Generalized hypervigilance" suggests that individuals who show heightened responsiveness to one sensory system also show hypervigilance to other modalities. However, research exploring the existence of generalized hypervigilance in healthy subjects is limited. Methods: We investigated whether hypervigilance to pain is associated with auditory stimuli in healthy subjects using the pain vigilance and awareness questionnaire (PVAQ) and auditory change‐related cortical responses (ACRs). ACRs are thought to reflect a change detection system, based on preceding sensory memory. We recorded ACRs under conditions that varied in terms of the accumulation of sensory memory as follows: short‐ACR, with short preceding continuous stimuli and long‐ACR, with long preceding continuous stimuli. In addition, the attention to pain (PVAQ‐AP) and attention to changes in pain (PVAQ‐ACP) subscales were evaluated. Results: Amplitudes of long‐ACR showed significant positive correlations with PVAQ‐ACP, whereas those of short‐ACR did not show any significant correlations. Conclusions: Generalized hypervigilance may be observed even in healthy subjects. ACR may be a useful index to evaluate the hypervigilance state in the human brain.